Angiosarcoma Arising from the Tongue of an 11-Year-Old Girl with Xeroderma Pigmentosum - Olson, Matthew T. (Springer US, 2011)
Xeroderma pigmentosum (XP) is a rare autosomal recessive defect in DNA endonuclease activity that is associated with the development of cutaneous malignancies, at sun exposed sites, including basal cell carcinoma, squamous cell carcinoma, and melanoma. Squamous cell carcinomas are also known to target the anterior tongue. Patients sometimes develop angiosarcomas, and these invariably arise from sun-exposed skin. A biopsy was taken from a large mass arising in the anterior tongue of an 11-year-old girl with XP and a history of cutaneous basal cell carcinomas. The histopathologic findings demonstrated a high grade epithelioid neoplasm resembling a poorly differentiated squamous cell carcinoma, but the immunohistochemical profile (AE1/AE3 negative, p63 negative, CD31 positive, CD34 positive) established the diagnosis of angiosarcoma. Angiosarcoma is an XP-related tumor that usually arises in sun-exposed skin but can also arise in the oral cavity. For patients with XP who develop epithelioid neoplasms of the oral cavity, epithelioid angiosarcoma should be considered in the differential diagnosis.